2015
DOI: 10.5847/wjem.j.1920-8642.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Lingual angioedema after alteplase treatment in a patient with acute ischemic stroke

Abstract: Lingual angioedema may appear as a possible complication in patients who were treated with alteplase. The management of these patients should be very careful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…A literature review demonstrated an overall small number of cases of unilateral angioedema secondary to tPA administration. This particular case had some similar characteristics to those cases [ 3 - 4 ]. The patient had stroke-like symptoms, but all imaging was negative for acute signs of an ischemic stroke.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A literature review demonstrated an overall small number of cases of unilateral angioedema secondary to tPA administration. This particular case had some similar characteristics to those cases [ 3 - 4 ]. The patient had stroke-like symptoms, but all imaging was negative for acute signs of an ischemic stroke.…”
Section: Discussionsupporting
confidence: 65%
“…A severe form of allergic reaction is angioedema, which is mediated by histamine or bradykinin release [ 2 ]. Angioedema results from the dilatation of the capillaries beneath the skin or mucosa, causing localized edema [ 3 - 4 ]. Angioedema occurring in the mouth (orolingual) or throat constitutes an airway emergency.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mode of action of antifibrinolytics in HAE, however, is not fully understood. It is known that an activation of the fibrinolytic system and the generation of plasmin, for example, by recombinant tissue PLG activator can lead to the formation of angioedema of the tongue . In HAEnCI with and without F12 gene mutations, low levels of PLG activator inhibitors 1 and 2 have been found, indicating a consumption by PLG activators (possibly tissue PLG activator (tPA) and urokinase PLG activator (uPA)) and underscoring the role of fibrinolysis …”
Section: Discussionmentioning
confidence: 99%
“…Acute onset macroglossia is well described within the literature as arising in numerous situations including patient positioning while under anesthesia, oropharyngeal packing, local trauma, postoperative from surgery in the oral cavity, or secondary to allergic or nonallergic angioedema [ 1 7 ]. Severe cases have the potential to present as an airway emergency due to oropharyngeal occlusion.…”
Section: Introductionmentioning
confidence: 99%